A Reflection on Civil Society Groups in Nigeria - Abang, Sunday Owen (NIU Journal of Humanities; Vol 3 No No. 2 (2018): KIU Journal of Humanities, Vol. 3 No. 2, June 2018, 2018)
This study examines the presence of civil societies in Nigeria, under both the military and civilian dispensations. It takes note of the role of the civil societies in their actions and inactions to government policies. Efforts are made to examine their roles at restoring, restructuring and being part of consolidating democracy in the Fourth Republic after long periods of military rule in the country. This is arguably the highest point of civil society actions in Nigeria. But, down the line, the study observed that there is proliferation of these civil societies in the country as a result of the fact that Sections 34-42 of the Constitution of the Federal Republic of Nigeria , 1999 (as amended) conferred certain fundamental rights on the Nigerian citizens, rights which were stretched to certain limits much to the chagrin of objectivity. This raises questions on the importance of civil societies as watchdogs of democracy. To carry out this research, data was sourced from literatures on civil society, journals, reputable textbooks through retrieval techniques, newspapers and other official documents. The data analyzed led to the recommendation that civil societies should be more proactive in playing their key roles in sustaining democracy and national development in Nigeria. Keywords: civil societies, military rule, civil rule, liberal approach, radical approach, democracy